Nonnegotiable shares, controlling shareholders, and dividend payments in China - Huang, Juan Juan; Shen, Yifeng; Sun, Qian (Journal of Corporate Finance, 2011)
China has some unique institutional features. For example, the shares of listed firms are segmented into negotiable and nonnegotiable ones. The controlling shareholders, usually connected to the government, hold nonnegotiable shares. We examine how these institutional features affected cash dividend payments in China during the period 1994–2006. We find that dividend payments are positively associated with the proportion of nonnegotiable shares in a firm and the proportion of nonnegotiable shares held by the controlling shareholder; moreover, the 2001 China Securities Regulatory Commission stipulation requiring cash dividend payments does not benefit negotiable shareholders. However, we also find that dividend payments are downside flexible, and controlling shareholders cannot force firms to pay or to pay more dividends when firms' earnings decline significantly. The conventional factors, especially profitability or the capability to pay, still play an important role in determining the dividend policy. The propensity to pay and the payout ratio in China are not high compared to those of other countries.